MULTI-OBJECTIVE OPTIMIZATION APPROACH TO OPERATIONAL PLANNING FOR THE ELECTRONIC WARFARE FORCE - Nguyen Duc, Định (Journal of Military Science and Technology, 2021)
In the stage of organizing and preparing for the campaign, the director of electronic warfare prepares a operational plan of the force, which determines the tasks for electronic warfare units. Tasks require the use of resources in terms of people and equipments. Tasks can be performed in parallel but are bound to each other. A plan is considered good if it simultaneously achieves optimal with basic objectives including: the shortest total execution time, the highest implementation efficiency and the average rate of resource used is the lowest. The paper proposes the multi-objective optimization approach to the operational planning problem and applies surrogate-assisted evolutionary algorithms with the adaptive guidance technique to find the optimal solutions.